A Near-Optimal Linear Crosstalk Precoder for Downstream VDSL - Cendrillon, R.; Ginis, G.; Van den Bogaert, E.; Moonen, M. (IEEE transactions on communications, 2007)
This letter presents a linear crosstalk precoder for very-high-speed digital subscriber lines (VDSL) that has a low run-time complexity. A lower bound on the data rate of the precoder is developed, and guarantees that the precoder achieves near-optimal performance in 99% of VDSL channels